Perforation of the right ventricle and inferior vena cava by bone cement after percutaneous vertebroplasty - Yan Dong; Yongfeng Zhu; Zhikun Fu; Yaping Xu; Xiangli Zhang (Medicine, 2026)
Rationale: Percutaneous vertebroplasty (PVP) is widely used to treat vertebral compression fractures. Although it is generally considered a minimally invasive procedure, leakage and systemic migration of polymethylmethacrylate bone cement may rarely occur and can cause potentially fatal cardiovascular complications. Intracardiac bone cement embolism accompanied by perforation of the right ventricle and inferior vena cava (IVC) is particularly uncommon. Patient concerns: A 70-year-old woman presented with palpitations and perioral numbness 2 months after undergoing PVP for an L4 vertebral compression fracture. Her vital signs were stable, and electrocardiographic findings and cardiac troponin levels were within normal ranges. Diagnoses: Echocardiography, coronary angiography, and computed tomography revealed linear bone cement fragments extending through the IVC, right atrium, and right ventricle. One intracardiac cement fragment had penetrated the right ventricular wall, leading to a diagnosis of cardiac cement embolism with right ventricular and IVC perforation. Interventions: Because of the risks of progressive myocardial perforation, cardiac tamponade, and other potentially fatal complications, the patient underwent surgical removal of the bone cement fragments with extracorporeal circulation. Both cement fragments were successfully removed, and the perforated right ventricular wall was repaired. Outcomes: The patient’s postoperative course was uneventful. Follow-up echocardiography before discharge showed no residual foreign body, pericardial effusion, or structural cardiac abnormality. Lessons: Intracardiac bone cement embolism should be considered in patients who develop unexplained cardiovascular symptoms after PVP, even when their hemodynamic status, electrocardiographic findings, and cardiac biomarkers are initially normal. Prompt multimodal imaging is essential for identifying the location and extent of cement migration. Timely surgical intervention should be considered when cardiac perforation, structural injury, or cardiac tamponade is suspected.